Legal Protection of Copyright as a Digital Asset in Technology-Based Commercial Transactions in Indonesia - Ariy khaerudin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The development of digital technology has driven the transformation of the global economy, including in Indonesia, through the commercialization of digital assets such as creative works, Non-Fungible Tokens (NFTs), and e-commerce platforms. However, the national legal system is still unable to accommodate these dynamics comprehensively. This study aims to analyze the effectiveness of legal protection of CopyrightCopyright as a digital asset in technology-based transactions, using normative legal methods and legislative, conceptual, and comparative legal approaches. The results of the study show that Law Number 28 of 2014 concerning Copyright and related regulations still has a gap in norms in dealing with new forms of digital intellectual property, weak law enforcement, and limited technical understanding by law enforcement officers. In addition, the less-than-optimal regulation in the financial, taxation, and personal data protection sectors increases the legal risks for digital economy actors, especially MSMEs and content creators. Therefore, responsive legal reforms are needed to strengthen the digital justice system, integrate technologies such as blockchain and AI, and increase legal literacy and coordination between institutions. This reform is important to create a fair, safe, and sustainable digital ecosystem that supports the growth of the national creative economy.